PENGARUH WARNA KASA PENUTUP AUTOCIDAL OVITRAP TERHADAP JLMLAH JENTIK NYAMUK AEDES AEGYPTI YANG TERTANGKAP - Joko Santoso; Retno Hestiningsih; Ratih Sari Wardani; Sayono - (Universitas Muhammadiyah Semarang, 2007)
Background: Aedes aegypti mosquito is one of the vectors which is able to infect Dengue Hemoryhagic Fever disease mechanically. The examination offree rate of mosquito lat-va in Putwotladi ttist-rict, Grobogai rege,cy,is amounting 86 o/o. One of the techniques to control the population of Aedes aegypti mechaiicallll i, iy installing autocidal ovitrap simply and economically. objective of the research is ti inow the effect i1 ,ori, gauze color autocidal ovitrap on the number of Aedes Aegypti lar-vie which are trappetl. Type of ie resiarch is explanatory research by using experimental research design with post-test only tlisrgn approach. The researchsubject is conductecl in the surroundings of Purwodacti dtitrict seitlement *tti olrrr